STRUCTURE OF THE MACROZOOBENTOS COMMUNITY IN THE NORTH COASTAL WATERS OF BENGKALIS ISLAND, RIAU PROVINCE - Saputri, Apriliana; Amin, Bintal; Yoswaty, Dessy (Asian Journal of Aquatic Sciences, 2021)
The macrozoobenthic community structure can be used as a bioindicator to determine water pollution. The macrozoobenthic community structure consists of species, abundance, diversity index (H '), dominance index (C) and species uniformity index (E). This research was conducted in July 2020 in the waters of the North Coast of Bengkalis Island. Water parameters measured include temperature, salinity and pH. In this study, it was divided into 3 stations, namely in Selat Baru Village (station 1), Jangkang Village (station 2) and Teluk Pambang Village (station 3). The results found that as many as 34 species from 4 classes of macrozoobenthos, namely Gastropods, Malacostraca, Bivalvia, and Merostomata. Gastropod class macrozoobenthos such as Volema pyrum, Littoraria scabra, Nassarius vibra, Drupella margariticola, Pirenella cingulata, and Nerita costata; from the Malacostraca class such as Uca dussumieri, Ocypode kuhlii, Clibanarius longitarsus, and Litopenaeus cetiferus; from the Bivalvia class such as Glauconome virens, Polymesoda expansa and Dinocardium robustum and from the Merostomata class such as Carcinoscorpius ratundicauda. The macrozoobenthic abundance values ​​from the three stations ranged from 0.01 to 1.29 Ind/m2, the diversity index value (H') ranged from 2.5589 to 2.8516, the dominance index value ranged from 0.2503 - 0.3312 and the uniformity index (E ) ranges from 0.6397 to 0.6838. Water quality parameters are as follows: temperature is 29-31°C, salinity ranges from 23-28 ppt, and pH ranges from 7.5-7.9. Sediment organic matter ranged from 6.88 to 11.26% and TSS ranged from 474-542 mg/L with the dominant sediment type at the three stations, namely sandy mud. This shows that the waters north of Bengkalis Island are classified as being polluted.